An overview of the concentrations and effects of metals in cetacean species - Bowles, David (J. Cetacean Res. Manage., 1999)
Data are presented on the hiomagnification rates, accumulation and concentrations of metals in cetacean species. Concentrations of metals predominantly occur in the soft tissues, although zinc and lead concentrate in the skin and bones. Rates of uptake are dependent upon metal availability, the species’ dietary preference and chemical reactions between contaminants. Differences in concentrations occur according to the sex and age of the animal, with certain metals displaying age-related trends. Mercury is the only metal which shows both biomagnification at all levels of the food chain and a positive correlation with age at all stages during a cetacean’s life. Differences in concentrations occur between baleen species and toothed cetaceans. Levels tend to be lower in baleen whales, primarily due to a shorter food chain (resulting in lower bioconcentration factors) and as the principal prey species are taken from lower parts of the food chain. A number of storage and detoxifying mechanisms have been recorded in many species that may alter the effects of high metal concentrations. Data on the effects of metal toxicity in cetacean species are sparse, but tolerance limits have been proposed for mercury and cadmium. These are compared with high concentrations recorded in certain species and possible effects extrapolated. Effects of toxicity may alter depending on the species, age and sex of the animal, but indications of toxic effects have been reported. Finally, the possibility of determining regional hot-spots, where background pollution levels are high, from concentrations of mercury reported in cetacean species, are examined.